Instructions
Differentiate both sides of the the equation using the chain rule. Differentiating both sides of the equation y^4 + 3y = 4x^3 + 5x + 1 results in the equation: 4y^3(y') + 3y' = 12x^2 + 5.
Manipulate the equation algebraically to isolate the y' terms on one side of the the equation, then simplify. For example, 4y^3(y') + 3y' = 12x^2 + 5 already has y' terms on one side of the equation but can be simplified to: (y')(4y^3 + 3) = 12x^2 + 5.
Solve for y' algebraically. For example, solving the equation (y')(4y^3 + 3) = 12x^2 + 5 for y' finds: y' = (12x^2 + 5) / (4y^3 + 3).
Substitute the x and y values of a coordinate point into the equation to determine the slope of the function at that point. For example, to find the slope of the point (3, 8) for the function f(x) = y^4 + 3y = 4x^3 + 5x + 1 with derivative f '(x) = y' = (12x^2 + 5) / (4y^3 + 3), substitute x and y into the equation: y' = 12(3)^2 + 5 / 4(8) + 3) = 108 + 5 / 32 + 3 = 113 / 35 = 3.2.